Application of design of experiments (DoE) optimization to the one-pot synthesis of 4, 6-dihydropteridinones. Issue 42 (9th September 2015) - Stone, Steven; Wang, Tiansheng; Liang, Jianglin; Cochran, John; Green, Jeremy; Gu, Wenxin
Abstract : A design of experiments (DoE) analysis of a tandem S n Ar-amidation cyclization reaction between 4-chloropyrimidin-5-amine and ( S )- N -methylalanine to form ( S )-7, 8-dimethyl-7, 8-dihydropteridin-6(5 H )-one is reported. Abstract : A design of experiments (DoE) analysis of a tandem S n Ar-amidation cyclization reaction between 4-chloropyrimidin-5-amine and ( S )- N -methylalanine to form ( S )-7, 8-dimethyl-7, 8-dihydropteridin-6(5 H )-one is reported. Five reaction variables were optimized using DoE and conversion was improved from 26% to 74%, with a significant reduction in reaction time while retaining high optical purity. The optimized conditions were applied to the synthesis of a wide variety of analogs and the expanded reaction substrate scope included a variety of amino acids and pyrimidines. Products were obtained in isolated yields up to 95% and enantiomeric excess as high as 98%.